Phenotypic differentiation among native, expansive and introduced populations influences invasion success - Adrián Lázaro‐Lobo; Angela T. Moles; Guillaume Fried; Filip Verloove; Juan Antonio Campos; Mercedes Herrera; Elena Goñi; Fréderic Bioret; Gabriella Buffa; Edy Fantinato; Alexander Sentinella; Myron P. Zalucki; et al. (Journal of Biogeography, 2021)
Aim Humans influence species distributions by modifying the environment and by dispersing species beyond their natural ranges. Populations of species that have established in disjunct regions of the world may exhibit trait differentiation from native populations due to founder effects and adaptations to selection pressures in each distributional region. We compared multiple native, expansive and introduced populations of a single species across the world, considering the influence of environmental stressors and transgenerational effects. Location United States Gulf and Atlantic coasts, United States interior, European Atlantic and Mediterranean coasts, east coast of Australia. Taxon Baccharis halimifolia L. (eastern baccharis). Methods We monitored seed germination, seedling emergence, survival and early growth in a common garden experiment, conducted with over 18,200 seeds from 80 populations. We also evaluated the influence of environmental stress and maternal traits on progeny performance. Results Introduced European Atlantic populations had faster germination and early growth than native populations. However, this was not the case for the more recently naturalized European Mediterranean populations. Introduced Australian populations grew faster than native populations in non‐saline environments but had lower survival in saline conditions commonly encountered in the native range. Similarly, expansive inland US populations germinated faster than coastal native populations in non‐saline environments but grew and germinated more slowly in saline environments. Maternal inflorescence and plant size were positively related with seed germination and seedling survival, whereas flower abundance was positively correlated with seedling early growth and survival. However, maternal traits explained a much lower fraction of the total variation in early demographic stages of B. halimifolia than did distributional range. Main conclusions Phenotypic differentiation could allow B. halimifolia to adapt to different biotic and abiotic selection pressures found in each distributional range, potentially contributing to its success in introduced and expansive ranges.